Quaternionic analysis and Maxwell‘s equations - Spr¨ossig, Wolfgang (CUBO, A Mathematical Journal, 2005)
Methods of quaternionic analysis are used to obtain solutions of Maxwell‘ s equations. By the help of time-discretisation Maxwell‘s equations are reduced to an equation of Yukawa type. Initial value and boundary value conditions are realized by a representation formula in each time step. Approximation and stability is proved.